Reliability and validity of Turkish version the penn alcohol craving scale (pacs) in male alcohol dependent inpatients - Evren, Cüneyt; Flannery, Barbara; Çelik, Rabia; Durkaya, Mine; Dalbudak, Ercan (Journal of Dependence, 2008)
Objective: The Penn Alcohol Craving Scale (PACS) is a 5-item self-rating scale developed by Flannery et al. (1999) for screening alcohol caraving. In the aim of this study, the reliability and validity of the Turkish translation of the PACS among alcohol dependent inpatients were determined. Method: The study was conducted with hospitalized patients between May 2007 and February 2008 in Bakirkoy State Hospital for Mental Health and Neurological Disorders, AMATEM (Alcohol and Drug Research, Treatment and Education Center) in Istanbul. One twenty two inpatients diagnosed as having alcohol dependence according to DSM-IV criteria were included in the study. They were given sociodemographic form and PACS and PACS was given again in one week period. The internal consistency of the Turkish version of PACS was evaluated by the Cronbach’s Alpha test. Results: In alcohol dependents the internal consistency coefficient (Cronbach’s alpha) was 0.88 for first evaluation and 0.94 for second evaluation. For each of the items, the corrected item-total correlation values were significant in the degree of p<0.001 in both evaluation. There was no difference between mean scores of two evaluations, whereas high positive correlation and kappa values were found. Among 5 items of PACS only 4th item (resistance) predicted relaps in two weeks. Conclusion: Wide spectrum of alcohol craving severity were found among inpatients. Results which were obtained in this study suggests that the Turkish version of the PACS could be used as reliable and valid for alcohol dependent inpatients.